2020
DOI: 10.1097/md.0000000000019966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraventricularly administered low-dose recombinant tissue plasminogen activator on interleukin 1-beta and transforming growth factor beta concentrations in cerebrospinal fluid of patients with primary intracerebral hemorrhage associated with intraventricular hemorrhage

Abstract: It is increasingly recognized that modulation of brain inflammation may uncover new potential therapeutic strategies for stroke. Recent studies have shifted focus from immunological implications in ischemic stroke to a more devastating form; the hemorrhagic stroke. The aim of this study was to investigate the neuroinflammatory response in cerebrospinal fluid in patients with primary intracerebral hemorrhage (ICH) associated with intraventricular hemorrhage (IVH) in the presence of low-dose recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Levels of IL-1α, TNF-α and IL-6 were relatively higher in CSF from control SAH patients compared to our observed very low levels in spontaneous IVH, whereas IL-1β was higher in our cohort. CSF IL-1β levels over first 7 days were even higher in a report of 41 adults with primary ICH associated with IVH who did not receive tPA [22]. Whether such comparisons are meaningful in a small sample, however, is not clear and may simply reflect sampling variation.…”
Section: Discussionmentioning
confidence: 91%
“…Levels of IL-1α, TNF-α and IL-6 were relatively higher in CSF from control SAH patients compared to our observed very low levels in spontaneous IVH, whereas IL-1β was higher in our cohort. CSF IL-1β levels over first 7 days were even higher in a report of 41 adults with primary ICH associated with IVH who did not receive tPA [22]. Whether such comparisons are meaningful in a small sample, however, is not clear and may simply reflect sampling variation.…”
Section: Discussionmentioning
confidence: 91%
“…While alteplase increases neutrophil degranulation and MMP-9 production, it also increases levels of protective tissue inhibitor of metalloproteinase [ 40 , 41 ] Alteplase also suppresses macrophage cytokine production dependent on NMDA-R expression. Sošić et al demonstrated an increased anti-inflammatory cytokine (TGF-β) compared with proinflammatory cytokine (IL-1β) response in the CSF in patients with primary ICH and IVH treated with recombinant tissue plasminogen activator [ 42 ]. Although alteplase increases all CSF leukocyte cell counts, its ability to suppress innate immune cell function and shift toward anti-inflammatory cytokine production may mitigate the effect of increased CSF leukocytes on mRS outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated an increased anti-inflammatory cytokine (TGF-β) compared with proinflammatory cytokine (IL-1β) response in the CSF in patients with primary ICH and IVH treated with recombinant tissue plasminogen activator [42]. Although alteplase increases all CSF leukocyte cell counts, its ability to suppress innate immune cell function and shift toward anti-inflammatory cytokine production may mitigate the effect of increased CSF leukocytes on mRS outcomes.…”
Section: Discussionmentioning
confidence: 99%